Confidentiality and Authenticity in a Platform Based on Network-on-Chip - Silva, Marcos Roberto; Zeferino, Cesar Albenes (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
In many-core systems, the processing elements are interconnected using Networks-on-Chip. An example of on-chip network is SoCIN, a low-cost interconnect architecture whose original design did not take into account security aspects. This network is vulnerable to eavesdropping and spoofing attacks, what limits its use in systems that require security. This work addresses this issue and aims to ensure the security properties of confidentiality and authenticity of SoCIN-based systems. For this, we propose the use of security mechanisms based on symmetric encryption at the network level using the AES (Advanced Encryption Standard) model. A reference multi-core platform was implemented and prototyped in programmable logic aiming at performing experiments to evaluate the implemented mechanisms. Results demonstrate the effectiveness of the proposed solution in protecting the system against the target attacks. The impact on the network performance is acceptable and the silicon overhead is equivalent to other solutions found in the literature.